Implementing a collaborative medicine and pharmacy educational activity in two countries. Issue 1 (1st January 2020) - Brock, Tina; Vu, Thao; Kadirvelu, Amudha; Lee, Chooi Yeng; Kent, Fiona
ABSTRACT: Background: To promote better collaboration for patient care, interprofessional education (IPE) is required in many health professions courses. However, successful IPE implementation at scale can be challenging because of complicated logistics and competing priorities. Implementing across multiple geographies adds further complexity. Objective: This paper describes the implementation of a full cohort IPE activity for medical and pharmacy students delivered at both the Australian and Malaysian campuses of Monash University. Design: We designed a 150-minute, blended learning activity centred around asthma care for second-year medical and pharmacy students. Student perceptions were measured with a pre- and post-activity survey using the validated ten-item, three-factor, SPICE-R2 instrument. Analysis focused on differences between professions and countries. Results: All second-year medicine (N = 301 in Australia and N = 107 in Malaysia) and pharmacy students (N = 168 in Australia and N = 117 in Malaysia) participated in the learning activity. A total of 326/693 (47%) students participated in the associated research by completing both the pre- and post-activity surveys. The pre-activity survey showed significant differences in four items between medicine and pharmacy students in Australia and two items in Malaysia. Post-activity, we observed significant changes in 8/10 items when the two professions were combined. Specifically, we noted changes across the countries in perceptions of roles and responsibilities for collaborative practice and patient outcomes from collaborative practice. Conclusions: IPE across different professions and countries is feasible. Positive outcomes in role understanding and perceived patient outcomes are achievable through a context-sensitive, locally driven approach to implementation. Longitudinal experiences may be required to influence perceptions of teamwork and team-based care.